Identification of a Novel Serum Proteomic Signature for Primary Sjögren’s Syndrome - Padern, Guillaume; Duflos, Claire; Ferreira, Rosanna; Assou, Said; Guilpain, Philippe; Maria, Alexandre Thibault Jacques; Goulabchand, Radjiv; Galea, Pascale; Jurtela, Maja; Jorgensen, Christian; Pers, Yves-Marie (Frontiers in Immunology, 2021)
Context: Primary Sjögren's syndrome (pSS) is a complex heterogeneous autoimmune disease (AID) which can mimic Rheumatoid Arthritis (RA) or Systemic Lupus Erythematosus (SLE). Our exploratory study investigated serum biomarkers that may discriminate pSS from RA and SLE. Methods: Serum concentrations of 63 biomarkers involved in immune cell trafficking, inflammatory response, cellular movement, and cell-to-cell signaling were measured in AID patients, included prospectively into the study at the Montpellier University Hospital. A multivariate analysis by multiple logistic regression was performed, and discriminative power assessed using logistic regression adjusted on significant demographic factors. Results: Among the 95 patients enrolled, 42 suffered from pSS, 28 from RA, and 25 from SLE. Statistical analysis showed that concentrations of BDNF (OR=0.493 with 95% CI [0.273-0.891]; p=0.0193) and I-TAC/CXCL11 (OR=1.344 with 95% CI [1.027-1.76]; p=0.0314) can significantly discriminate pSS from RA. Similarly, greater concentrations of sCD163 (OR=0.803 with 95% CI [0.649-0.994]; p=0.0436), Fractalkine/CX3CL1 (OR=0.534 with 95% CI [0.287-0. 991]; p=0.0466), MCP-1/CCL2 (OR=0.839 with 95% CI [0.732-0.962]; p=0.0121), and TNFa (OR=0.479 with 95% CI [0.247-0.928]; p=0.0292) were associated with SLE diagnosis compared to pSS. In addition, the combination of low concentrations of BDNF and Fractalkine/CX3CL1 was highly specific for pSS (specificity 96.2%; positive predictive value 80%) compared to RA and SLE, as well as the combination of high concentrations of I-TAC/CXCL11 and low concentrations of sCD163 (specificity 98.1%; positive predictive value 75%). Conclusion: Our study highlights biomarkers potentially involved in pSS, RA, and SLE pathophysiology that could be useful for developing a pSS-specific diagnostic tool.